Contemporary Structural Changes in Irkutsk as a Siberian Regional Centre - Jakobson, Anatol Yakovlevich; Batsun, Natalia V. (Studies of the Industrial Geography Commission of the Polish Geographical Society, 2015)
Much that has been taking place in today’s Irkutsk is quite typical for cities of post-Soviet Russia. Irkutsk is suffering from drastic structural changes: in its macro-geographic position and international links, in the structure of production, in its postindustrial (non-production) functions, in the system of regional development. The total estimation of changes should be positive. But we can see a lot of losses. Some of them seem to be temporary, but there are also losses caused by the market character of the reforms themselves.